Effects of 3 mg/kg body mass of caffeine on the performance of jiu-jitsu elite athletes - Merino-Fernández, M.; Giráldez-Costas, V.; González-García, J.; Gutiérrez-Hellín, J.; González-Millán, C.; Matos-Duarte, M.; Ruiz-Moreno, C. (Nutrients, 2022)
The effects of caffeine were investigated in judo, boxing, taekwondo and Brazilian jiu-jitsu. However, this substance was never investigated regarding traditional jiu-jitsu. Therefore, the aim of this research was to analyze the effects of caffeine in the Special Judo Fitness Test (SJFT) and technical variables during combat in traditional jiu-jitsu elite athletes. Methods: Twenty-two young professionals of traditional jiu-jitsu, 11 men and 11 women (age = 22 ± 4 (18-33) years, body mass = 66.6 ± 10.8 (46.2-86.1) kg, height = 1.70 ± 0.9 (1.55-1.85) m) with 15 ± 7 years of experience in traditional jiu-jitsu, participated in a double-blind, counterbalanced, crossover study. In two different conditions, the traditional jiu-jitsu athletes ingested 3 mg/kg body mass of caffeine or a placebo. After 60 min, they performed the SJFT test to measure throwing performance, and subsequently, combat to analyze offensive and defensive hitting techniques. Results: Caffeine had a main effect on the number of throws during the SJFT test (P < 0.01). In addition, it was effective in sets 2 (13 ± 2 vs. 14 ± 2; p = 0.01) and 3 (12 ± 2 vs. 13 ± 1; p = 0.03). There was also a main effect during the test on heart rate when caffeine was ingested (F = 12.48, p < 0.01). The effects of caffeine were similar compared to the placebo condition regarding performance during combat both in offensive and defensive fighting variables Conclusions: the pre-exercise ingestion of 3 mg/kg body mass of caffeine increased performance in the SJFT test, decreased fatigue perception, and increased power and endurance perception in professionally traditional jiu-jitsu athletes. However, it did not seem to improve offensive and defensive technical actions during combat.